2017
DOI: 10.3389/fmicb.2017.01488
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing and Targeted Mutagenesis Reveal Virulence Contributions of Tal2 and Tal4b of Xanthomonas translucens pv. undulosa ICMP11055 in Bacterial Leaf Streak of Wheat

Abstract: Bacterial leaf streak caused by Xanthomonas translucens pv. undulosa (Xtu) is an important disease of wheat (Triticum aestivum) and barley (Hordeum vulgare) worldwide. Transcription activator-like effectors (TALEs) play determinative roles in many of the plant diseases caused by the different species and pathovars of Xanthomonas, but their role in this disease has not been characterized. ICMP11055 is a highly virulent Xtu strain from Iran. The aim of this study was to better understand genetic diversity of Xtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 101 publications
2
47
2
Order By: Relevance
“…TALE genes have been identified from three X . translucens strains with a complete genome sequence as well as a few strains with a draft genome sequence (Pesce et al , ; Jaenicke et al ., ; Peng et al , ; Charkhabi et al , ). X .…”
Section: Virulence and Pathogenicity Of X Translucensmentioning
confidence: 99%
See 4 more Smart Citations
“…TALE genes have been identified from three X . translucens strains with a complete genome sequence as well as a few strains with a draft genome sequence (Pesce et al , ; Jaenicke et al ., ; Peng et al , ; Charkhabi et al , ). X .…”
Section: Virulence and Pathogenicity Of X Translucensmentioning
confidence: 99%
“…Sequence comparison revealed that the two strains had several unique RVDs, including KG, QD, Y*, YK and YD, which have not been identified from other Xanthomas spp. (Peng et al , ; Charkhabi et al , ). It was also found that some TALEs that are widely distributed in other xanthomonads are less frequently present in X .…”
Section: Virulence and Pathogenicity Of X Translucensmentioning
confidence: 99%
See 3 more Smart Citations